2019
DOI: 10.1021/acs.chemmater.9b03898
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free Synthesis and Thin-Film Deposition of Cesium Copper Halides with Bright Blue Photoluminescence

Abstract: Non-toxic alternatives to lead halide perovskites are highly sought after for applications in optoelectronics. Blue-luminescent materials are especially demanded as they could be used to prepare white light-emitting diodes, with important potential applications in lighting systems. However, wide bandgap blue emitters with high photoluminescence quantum yields (PLQY) are typically more difficult to obtain as compared to green-or red-emitting ones. Here, we prepared two series of inorganic cesium copper halides,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 37 publications
(90 reference statements)
5
83
1
Order By: Relevance
“…The Rietveld refinement of the powder XRD pattern indicated that Cs 3 Cu 2 Cl 5 adopts space group Cmcm ( a = 15.449[5] Å, b = 8.7562[3] Å, and c = 8.6814[3] Å) (see Tables S8–S10, Supporting Information), which is different from the I and Br analogs ( Pnma ), as shown in Figure 1d,e. [ 21–23 ] For the Cs 3 Cu 2 Cl 5 , each Cu + ion has been coordinated with three Cl − ions and adopted a near‐planar configuration. Through Cl corner sharing, two [CuCl 3 ] 2− units formed an isolated folded dimer [Cu 2 Cl 5 ] 3− with a 75.51° face angle.…”
Section: Figurementioning
confidence: 99%
“…The Rietveld refinement of the powder XRD pattern indicated that Cs 3 Cu 2 Cl 5 adopts space group Cmcm ( a = 15.449[5] Å, b = 8.7562[3] Å, and c = 8.6814[3] Å) (see Tables S8–S10, Supporting Information), which is different from the I and Br analogs ( Pnma ), as shown in Figure 1d,e. [ 21–23 ] For the Cs 3 Cu 2 Cl 5 , each Cu + ion has been coordinated with three Cl − ions and adopted a near‐planar configuration. Through Cl corner sharing, two [CuCl 3 ] 2− units formed an isolated folded dimer [Cu 2 Cl 5 ] 3− with a 75.51° face angle.…”
Section: Figurementioning
confidence: 99%
“…Sebastia‐Luna et al successfully synthesized β‐Cs 3 Cu 2 Cl 5 , and found that the structure of β‐Cs 3 Cu 2 Cl 5 metamorph rapidly in the air, which illustrates that the β‐Cs 3 Cu 2 Cl 5 synthesized using the general method was unstable. [ 26 ] According to the structure diagram, [Cu 2 Cl 5 ] 3− chain is the basis of β‐Cs 3 Cu 2 Cl 5 , and Cs + fills in the gaps in the [Cu 2 Cl 5 ] 3− chain, as shown in Figure 2b. Therefore, we infer that the role of hypophosphorous acid is to stabilize [Cu 2 Cl 5 ] 3− skeleton and ensure the stable existence of β‐Cs 3 Cu 2 Cl 5 structure.…”
Section: Resultsmentioning
confidence: 99%
“…[ 23,24 ] The 1D β‐Cs 3 Cu 2 Cl 5 containing nontoxic and earth‐abundant elements, was reported as a cyan‐green phosphor, but the β‐Cs 3 Cu 2 Cl 5 with high PLQY(>90%) powders usually prepared by complex methods and environmental unfriendly organic solvent were used during their complex synthesis (Table S1, Supporting Information). [ 25–29 ] Although neither Sebastia‐Luna et al and Xie et al did not use any organic solvents, their synthetic samples of PLQY were up to 81%. Therefore, it is necessary to explore a simple and environmental‐friendly synthetic method for large‐scale preparation of β‐Cs 3 Cu 2 Cl 5 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 31–33 ] By the addition of appropriate organic molecules, it is possible to synthesize perovskite nanocrystals. [ 34 ] Furthermore, the mechanochemical synthesis of lead‐free perovskites based on tin, [ 16,35,36 ] copper, [ 37 ] or bismuth [ 38 ] on the B position was demonstrated as well. Mechanochemistry is a solvent‐free synthesis method.…”
Section: Halide Perovskites In Powder Formmentioning
confidence: 99%